2020
DOI: 10.3390/su12051757
|View full text |Cite
|
Sign up to set email alerts
|

A Didactic Pedagogical Approach toward Sustainable Architectural Education through Robotic Tectonics

Abstract: Robotic tectonics have been integrated into the architectural profession through automated construction for more than a decade, advancing sustainability initiatives in the industry and increasing the quality of building construction. Over the years, avant-garde architects have explored the feasibility of this new design paradigm through the integration of newly-developed digital design software into automated construction. This robotic digital workflow continues to push designers to re-think the complete archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the mapping, the study separated this studio model into two categories to differentiate between building technologies used in the workshop: Design-build and design-fabricate. While design-to-fabricate workshops allow students to explore the potentials of computational design processes combined with new fabrication technologies "to make automated construction a reality (Shi et al, 2020)", most design-build workshops are organized for communities with low income affected by political and natural disasters living in rural areas that are not accessible to architectural services. In these workshops, sustainable, recyclable, or salvaged materials can be obtained locally, easily, and cheaply (Guner et al, 2017, p. 6868).…”
Section: Design Studio: Hands-on (Design-build and Design-fabricate)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the mapping, the study separated this studio model into two categories to differentiate between building technologies used in the workshop: Design-build and design-fabricate. While design-to-fabricate workshops allow students to explore the potentials of computational design processes combined with new fabrication technologies "to make automated construction a reality (Shi et al, 2020)", most design-build workshops are organized for communities with low income affected by political and natural disasters living in rural areas that are not accessible to architectural services. In these workshops, sustainable, recyclable, or salvaged materials can be obtained locally, easily, and cheaply (Guner et al, 2017, p. 6868).…”
Section: Design Studio: Hands-on (Design-build and Design-fabricate)mentioning
confidence: 99%
“…Cabral Filho ( 2005) accounts for the role of a series of experimental workshops to include an artistic approach to the work in a computer lab dedicated to teaching and researching architecture. Shi et al (2020) organized four "Robotic Tectonics" workshops to develop a new didactic pedagogical approach that relies on robotic tectonics principles. Among the reviewed workshops, the study determined that problem-based learning workshops are an ideal mix of practice, research, and education and balance "situations in which the transfer of practice into faculty programs influences the development of education in the form of an architecture office where educational criteria do not take priority (Momirski, 2019).…”
Section: Research and Education: Inspirationsmentioning
confidence: 99%
“…The use of algorithms and parametric design, as well as other digital technology such as computerized numerical control (CNC) fabrication and 3D printing, has made it possible to transform environmental concerns into architectural elements such as form, space, and structure, as well as built objects. Such technology provides the opportunity to integrate sustainable design into the entire architectural design process [19,21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These observations are consistent with previous studies of the teaching of digital design in architecture, which examined the subject from different perspectives, such as architectural expression, the design software used, and the inclusion of BIM, digital fabrication, and material performance. Some studies found that different design software was more prominent in different areas of design; for example, the use of computer aided design (CAD) was largely restricted to the visual representation of student conceptual designs [41], BIM was used in courses that focused on the systematic concept of architectural design [16], and digital fabrication was used in courses that focused on the expression and understanding of relationships between structure, material and form [22,25,42].…”
Section: Levels Of a Digital Architectural Design Program Modulementioning
confidence: 99%
See 1 more Smart Citation